The Effect of Affiliated Motivation, Work Environment, Competency, and Affective Commitment on Performance of Transportation Service Officers, Labuhanbatu District - Dian Prasetyo; P. Pitriyani; Fauziah Hanum (Quantitative Economics and Management Studies, 2022)
Study this conducted To use analyze influence from motivation affiliate, environment work, competence and commitment affective to performance employee at the Department of Transportation Regency Labuhanbatu . Study this use method quantitative. Result of study this show that all independent variables give influence positive and significant to performance employee good by simultaneous nor partial. That thing proved with results from the t test and F test of the study. t test showing results from variable motivation affiliated (X 1) has score t arithmetic (4.55) > t table ( 1.66 ) which means H a accepted and H o rejected with score significant more small from score probability 0.05 or score significant 0.000 < 0.05, then could concluded that variable motivation affiliate (X 1 ) influential positive and significant to performance employee . Environment work (X 2) has score t count (5.41) > t table (1.66) which means Ha is accepted and Ho is rejected with score significant more small from probability 0.05 or 0.000 < 0.05 then could concluded that environment work (X 2 ) has an effect positive and significant to performance employee . Competence (X 3 ) has score t arithmetic (9.62) > t table ( 1.66) which means Ha is accepted and Ho is rejected , with score significant more small from probability 0.05 or 0.000 < 0.05, then could concluded that competence (X 3 ) has an effect positive and significant to performance employee . Commitment affective (X 4 ) has score t count (13,42) > t table ( 1.66) which means Ha is accepted and Ho is rejected with score significant more small from probability 0.05 or 0.000 < 0.05 then could concluded that commitment affective (X 4 ) influential positive and significant to performance employee. F value count in table 6 which is 155.27 > F table 2.48 with score significance 0.000 < 0.05. The result shows that motivation affiliate, environment work, competence and commitment affective by simultaneous have influence positive and significant to performance employee.